Volume 2A: 41st Design Automation Conference 2015
DOI: 10.1115/detc2015-47290
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Operation Decisions in Net Zero Building Clusters

Abstract: In light of the growing strain on the energy grid and the increased awareness of the significant role buildings play within the energy ecosystem, the need for building operational strategies which minimize energy consumption has never been greater. One of the major hurdles impeding this realization primarily lies not in the lack of decision strategies, but in their inherent lack of adaptability. With most operational strategies partly dictated by a dynamic trio of social, economic and environmental factors whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Todas estas oportunidades técnicas se pueden aplicar de manera local en los países para edificaciones individuales o grupo de edificaciones que se complemente entre sí. En los últimos años, la creciente aplicación de nZEB ha aumentado el interés en los edificios de próxima generación llamados comunidad de edificios de energía casi nula (grupos nZEB) [106]. La comunidad nZEB se basa en un concepto de colaboración en el que los nZEB pueden compartir libremente sus generaciones de energía renovable, almacenamiento e información entre ellos dentro de la comunidad [107].…”
Section: Campus Universitarios Zec)unclassified
“…Todas estas oportunidades técnicas se pueden aplicar de manera local en los países para edificaciones individuales o grupo de edificaciones que se complemente entre sí. En los últimos años, la creciente aplicación de nZEB ha aumentado el interés en los edificios de próxima generación llamados comunidad de edificios de energía casi nula (grupos nZEB) [106]. La comunidad nZEB se basa en un concepto de colaboración en el que los nZEB pueden compartir libremente sus generaciones de energía renovable, almacenamiento e información entre ellos dentro de la comunidad [107].…”
Section: Campus Universitarios Zec)unclassified
“…With reference to a number of studies introducing the new electricity network [41,103,104], a generic power distribution network, which represents the future development trend of micro power network for multiple energy prosumers and the public charging stations, is summarized in this study, as shown in Figure 7. The energy prosumers are equipped with their own renewable energy systems, electrical storage, EVs and other electrical appliances.…”
Section: Local Microgrid Structurementioning
confidence: 99%
“…Then, based on the optimized performances at the building cluster level, the operation of every single building inside the cluster is coordinated using a non-linear programming algorithm. Similarly, Odonkor et al, developed a control method for NZEBs using a genetic algorithm and Pareto decision making based on an adaptive bi-level decision model (with a facilitator agent at the cluster level and local systems at the single NZEB level) [104]. Considering the dynamic pricing, in [24] a similar three-step iterative demand response control algorithm is developed.…”
Section: Coordinated Controlsmentioning
confidence: 99%
“…To achieve energy sharing among buildings, existing studies have developed a number of advanced controls. For example, Odonkor et al proposed a control method of ZEBs using genetic algorithm and Pareto decision making based on an adaptive bi-level decision model (with a facilitator agent at cluster level and local systems at single NZEB level) [11]. In such bi-level decision model, the individual building's systems (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…𝑖 𝑗 𝑗 1 (11) (ii) For each single building, the electricity charging amount must be smaller than the remaining storage capacity of the battery, and the electricity discharging amount must be smaller than the amount of electricity stored in the battery. There are 2N inequality constraints for N buildings.…”
mentioning
confidence: 99%